2010
DOI: 10.1542/peds.2009-1486
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Control in Pediatric Type 1 Diabetes: Role of Caregiver Literacy

Abstract: Literacy and numerical skills of caregivers significantly influence glycemic control of their children with type 1 diabetes. Assessing literacy/numeracy skills of caregivers and addressing these deficiencies may be crucial in optimizing glycemic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 19 publications
4
55
0
4
Order By: Relevance
“…In this study, 18.5% of parents were assessed as having low health literacy, similar to the estimate of 17% reported for a previous sample of parents of children with type 1 diabetes (Hassan & Heptulla, 2010). Although the 18.5% prevalence rate of low health literacy for the parents in this study falls within the rates of 1-29% reported for a variety of parent samples (DeWalt, Dilling, Rosenthal, & Pignone, 2007;Driessnack, Chung, Perkhounkova, & Hein, 2013;Kumar et al, 2010;Otal et al, 2012;Wittich, Mangan, Grad, Wang, & Gerald, 2007;Yin et al, 2009), it is lower than the 28.7% prevalence rate reported for a national sample of parents (Yin et al, 2009).…”
Section: Prevalence Of Low Health Literacysupporting
confidence: 87%
See 2 more Smart Citations
“…In this study, 18.5% of parents were assessed as having low health literacy, similar to the estimate of 17% reported for a previous sample of parents of children with type 1 diabetes (Hassan & Heptulla, 2010). Although the 18.5% prevalence rate of low health literacy for the parents in this study falls within the rates of 1-29% reported for a variety of parent samples (DeWalt, Dilling, Rosenthal, & Pignone, 2007;Driessnack, Chung, Perkhounkova, & Hein, 2013;Kumar et al, 2010;Otal et al, 2012;Wittich, Mangan, Grad, Wang, & Gerald, 2007;Yin et al, 2009), it is lower than the 28.7% prevalence rate reported for a national sample of parents (Yin et al, 2009).…”
Section: Prevalence Of Low Health Literacysupporting
confidence: 87%
“…Hassan & Heptulla (2010) found that children of parents with inadequate health literacy had significantly poorer diabetes control compared to those with parents with adequate health literacy 22 (hemoglobin A1C 10.4 % vs. 8.6% respectfully, p< .001). In contrast, in a cross sectional study examining mediator variables between literacy and diabetes control, found no relationship between health literacy and hemoglobin A1C levels, suggesting a weaker relationship.…”
Section: Parent Health Literacy and Diabetes Outcomesmentioning
confidence: 89%
See 1 more Smart Citation
“…The incidence of T1DM varies greatly between different countries, within countries, and between different ethnic populations (1). Because of the potentially life threatening sequels of uncontrolled T1DM, the optimal control of glucose level is very important for the diabetic children (1)(2)(3)(4). Increases in diabetes prevalence and treatment costs have led to a growing number of studies for controlling this disease.…”
Section: Introductionmentioning
confidence: 99%
“…However, this line of reasoning is generally supported by our emerging understanding of how health literacy affects health outcomes for diseases such as diabetes, which require a high degree of selfmanagement. Findings suggesting that health outcomes are influenced by the literacy of family members, 18 that health literacy influences family support, 19 and that literacy is associated with social isolation are just a few examples of the complex relationships currently being explored. 20 In response, expert clinical and health literacy researchers have recently called for the health literacy community to adopt an even more comprehensive definition of health literacy, which not only takes into account patients' reading and numeracy skills, but also considers evidence of how a broad range of cognitive and psychosocial factors-such as confidence, engagement, problem-solving, and social support-are associated with patients' ability to successfully engage in self-management behaviors.…”
Section: -14mentioning
confidence: 99%